Amniotic fluid glial fibrillary acidic protein (AF‐GFAP), a biomarker of open neural tube defects. (28th July 2013) - Lopez, Jonathan; Mikaelian, Ivan; Gonzalo, Philippe
ABSTRACT Objective Neural tube defects (NTDs) are usually identified by ultrasonography and confirmed by alpha‐fetoprotein (AFP) assay and acetylcholinesterase (AchE) electrophoresis in amniotic fluid. Yet, both of these biomarkers can be found positive in other etiologies. Here, amniotic fluid glial fibrillary acidic protein (AF‐GFAP), which was identified by a proteomic study, is shown to be a useful biomarker for NTD diagnosis. Method Amniotic fluid glial fibrillary acidic protein was measured by an ELISA assay in 138 cases of NTDs. Seventy samples from normal pregnancies used as controls and 27 samples giving false positive or false negative results either for AchE or AFP and corresponding to fetal death (n = 8), gastroschisis (n = 8), and unexplained etiologies (n = 11) were also tested. Results Whatever the gestational age, GFAP was below 0.2 ng/mL in control samples, whereas 99.1% of open NTDs (29/29 in the anterior NTD group and 80/81 in the spina bifida group) were above this threshold. Closed NTDs were all negative (28/28). None of the other samples tested were positive, except in case of fetal death (8/8). Conclusions Amniotic fluid glial fibrillary acidic protein is a sensitive biomarker for open NTD diagnosis with a good negative predictive value for closed NTD. Compared with AFP and AchE, our results indicate that AF‐GFAP alone is more efficient than this classical association. © 2013 John Wiley & Sons, Ltd.